Quantitative Method for Evaluating Shale Oil Resources Based on Movable Oil Content - Zhao Xianzheng; Pu Xiugang; Jin Fengming; Han Wenzhong; Shi Zhannan; Zhang Wei; Dong Xiongying; Wang Hu; Li Haodong (Geofluids)
The light hydrocarbon content (S1) of shale oil is lost in aboveground experimental measurements, which do not accurately reflect actual underground light hydrocarbon content and cannot meet the demands of resource quantity calculation. Based on field and laboratory experimental data from the second member of the Kongdian Formation in the Cangdong Sag, Bohai Bay Basin, the retained oil and movable oil contents in shale were calculated using a mathematical formula, and the total resources were quantified. The correction coefficient of S1 from pyrolysis and the adsorption of oil by the total organic carbon (TOC) were determined to be 1.25 and 100 mg/g, respectively. The calculated parameter movable oil content (Smovable) and the corresponding calculation formula of S1 are proposed. The lower limit of S1 is 100 mg HC/g rock, the TOC content is 4 wt % and 6 wt %, and the corrected movable oil content of 3 mg/g and 6 mg/g, respectively, will be of great significance in shale oil geology and engineering. The optimal geological and engineering settings are divided into three categories and eight subcategories on the basis of these findings. Methods for evaluating total, movable, and recoverable oil resources from shale are discussed, which elucidate a new method for quantitative evaluation and ranking of shale oil resources. This approach is suitable for application in other shale oil exploration and development areas globally.